Utilizing Facebook as a Learning Media: Social Media Engagement in Students’ Descriptive Writing - Memei Meilani; Mutiarani Mutiarani (Syntax Idea, 2022)
This study aims to find out the effectiveness of Facebook in students’ descriptive writing. The writer applied the pre-experimental method with one group pre-test and post-test designs, and collected data based on the test. The data was analyzed statistically using SPSS 22. The sample of the research was the tenth grade students of SMK Bina Insan Tangerang consisting of 20 students. The sample was taken by using simple random sampling technique. The result of the calculation shows that the mean score of the students on the post-test is higher than on the pre-test. Where in the pretest students got 70.45 while in the post-test they reached 86.35. Based on the statistical calculation with the significance level of 5%, t-test (9.133) was higher than t-table (2.093). It means that there was a significant difference. Therefore H0 was rejected and H1 was accepted. It indicated that Facebook is effective in students’ descriptive writing.